Presentation of a new multifunctional oral cavity simulator : the “MOCS” - Maske, Tamires Timm (2025)
This article describes a new multifunctional oral cavity simulator (MOCS) that allows, with little technical support and easy handling, the laboratory development of dental hard tissue lesions under clinically similar conditions. The MOCS consists of a heating unit containing three independent cylindrical chambers with three specimen holders inside. Liquids flow through the surfaces of specimens by inlets on the lid of the chamber, which is connected to a medium/artificial saliva source through a computer-controlled peristaltic pump. The design, operational principles, and clinical application of this simulator, such as microcosm-induced development of carious-like lesions, acidic-induced erosion-abrasion like-lesions, and testing the anticariogenic effect of restorative materials, are shown. The MOCS can mimic several aspects of the oral cavity, being a promising device for assessing dental hard tissue lesions.